A social ecological, relationship-based strategy for parent involvement: Families And Schools Together (FAST). Issue 3 (21st September 2015) - Tracey Bywater, Dr; McDonald, Lynn; Miller, Hannah; Sandler, Jen
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – Most schools struggle to get busy and stressed parents to come repeatedly to the school building for events. At primary schools, especially those with pupils living in low-income communities or with many immigrants, involving parents to come at all is seen as a challenge. The purpose of this paper is to present a social ecological strategy of using the school building as a site for families to gather and for community networks to grow by building relationships between parents who have same-aged children attending that school. When families know other families, they feel more comfortable coming into the school building, and probably will return frequently. Design/methodology/approach – A large randomised controlled trial of 52 urban schools with an average of 73 per cent Latino students situated in disadvantaged neighbourhoods in the USA has data to examine the impact of this strategy on parent involvement. Parents of all first-grade students (age 6 or 7) at schools assigned either to Families and Schools Together (FAST) or services-as-usual were invited to participate. At schools with the social ecological strategy universal invites were made to those in the study to attend any one of eight weekly multi-family group sessions offered after-school at the building. Trained teams were culturally representative of the families (language, ethnicity) and made up of local parents and professionals; each team hosted up to ten families in a hub for two and a half hours (83 families attended at one session). Parents were socially included, treated with respect, coached by the team to lead a family meal, singing, family crafts and games at a family table. Parent time (respite) was provided with chat-time in pairs, followed by parent-led discussion groups. Parents were coached in one to one time, "child-led" responsive play for 15 minutes. Findings – Parent involvement data showed that on average, 43.6 per cent of all first-graders' families (an average of 44 families per school) attended at least one session; of those, who attended at least one session, 69 per cent returned for another. On average, of those families who attended at least once, the average family went four times; an average of 22 families per school attended six or more sessions. Parent graduates led monthly booster sessions open to all families. In half of the families, both fathers and mothers attended; immigrant parents attended statistically significantly more than native-born ones. In surveys, more parents in schools with FAST vs control reported attending three or more events at school. Practical implications – The FAST programme encourages the involvement of reluctant parents in school events. This benefits both children's general well-being and academic attainment and so contributes to preventative public health strategies. Originality/value – This paper brings new perspectives to the challenges faced by educators in involving parents at school by a sociologist-led research team introducing a social worker-developed social ecological, systemic strategy to schools in low-income communities using a randomised controlled design. This novel social ecological approach has consistently and effectively engaged whole families into increased involvement in schools in 20 countries, especially in low-income communities. Headteachers consistently report increased school engagement of FAST parent graduates for years, suggesting that the early intensity builds ongoing relationships of trust and reciprocity across home, school and community. Policy makers should note that building social capital in disadvantaged communities through partnerships with parents and schools can result in decreased disparities in health, social care and education.